PENGGUNAAN GAS AIR MATA DALAM PENGAMANAN PERTANDINGAN SEPAKBOLA DALAM PERSPEKTIF HUKUM POSITIF DI INDONESIA - Putra, Dery Irawan Aditya; Zeinudin, Moh.; Fithry, Abshoril (Jurnal Jendela Hukum, 2023)
Result observationaling to point out 1. FIFA'S order and also PSSI was clear about sharp weapon purpose and Lachrymator may not be brought in evenless is utilized at deep stadium and also stadium outboard, that thing most decants deep section 19b. " No. fire arms or crowd control gases shall be carried or used (May not take in or utilizes firearm or lachrymator),", 2. forbidden FIFA order marks sense lachrymator, therefore law accountability did by football chairman or at so-called Indonesia with PSSI and Panita Is Executor or Panpel. But, since at oft lachrymator purpose Indonesia did by agency, therefore agency is mustinya even do law accountability as it were has already been brought together deep Section 13 Kapolri's regulations Number 1 Years 2009. FIFA'S conclusion and PSSI was clear forbidden deep water gas purpose because will trouble eye health stops the show.